Tantangan Desentralisasi Fiskal Era UU HKPD: Tinjauan Kepustakaan atas Implikasi Resistensi Wajib Pajak Kendaraan Bermotor terhadap Kapasitas Keuangan Kota Semarang (Dharma Ekonomi, 2026)
The implementation of regional autonomy and fiscal decentralization aims to enhance local governments' financial independence. However, fiscal imbalances between the central and regional governments led to the enactment of Law Number 1 of 2022 (UU HKPD), designed to strengthen regional fiscal capacity. This law introduces a piggyback tax system through a surcharge on the Motor Vehicle Tax. This study analyzes the dynamics of the piggyback tax system in Semarang City, focusing on the implications for taxpayer resistance and regional financial capacity. Using a descriptive qualitative approach, the study reviewed secondary data from regulatory documents, financial reports, and academic literature. The findings show that the shift towards centralistic fiscal policies and the increase in tax burdens have sparked significant taxpayer resistance. This resistance occurs both passively, due to poor regulatory literacy, and actively, through delays in tax payments. The resistance damages the psychological contract between the state and citizens, undermining local financial stability. It risks reducing local revenue, increasing tax collection costs, and limiting fiscal space for infrastructure development. The study suggests that Semarang’s government needs to adopt an adaptive governance framework with transparent tax allocation, digitalization of services, and persuasive policies to restore public trust and encourage compliance.